Principal’s Leadership Practices in Fostering a Learning Community at Pelangi Islamic Elementary School - Fatwa, Alyan; Amilia, Winanda; Japar, Muhammad; Herdiati, Dian; Abdurrosyid (Indonesian Journal of Islamic Elementary Education, 2025)
This article discusses the leadership of elementary school principals. Pelangi Islam Elementary School is a formal educational institution for elementary level.The principal is the central figure in the elementary school. The principal is not only a teacher, but also a leader who guides students in understanding and practicing Islamic education. The Principal's leadership plays an important role in building a student learning community that does not only focus on academic aspects, but also on developing character and spirituality. This research aims to analyze the leadership role of the Principal in creating a supportive learning environment for students at Pelangi Islam Elementary School. To identify the strategies used by the Principal in building collaboration and positive interactions between students. This research used qualitative methods at Pelangi Islamic Elementary School, Tegal. The Principal's leadership has a significant impact in building a student learning community at Pelangi Tegal Islamic Elementary School. With a collaborative and integrative approach, the Principal can create an environment that supports students' academic and character development. Further research is needed to dig deeper into the most effective strategies in different contexts.